Antecedents of the Green Behavioral Intentions of Hotel Guests: A Developing Country Perspective - Saleem, Farida (Sustainability, 2021)
The current study sought to extend the literature on antecedents of the green behavioral intentions of hotel guests in a developing country context. Building on the theory of planned behavior and moral norm-activation theory, antecedents of the green behavioral intentions of hotel guests were proposed and tested using a developing country as a field of study. Data were collected from 203 hotel guests, and the proposed model was analyzed using a structural equation modeling technique. The results showed that altruism helps in developing positive attitudes, and these attitudes have a significant influence on hotel guests’ green behavioral intentions. Similarly, cognitive aspects, including quality attributes and value for money, also play a role in developing positive intentions for willingness to pay more and revisit intentions. Inconvenience has a significant negative impact on revisit intentions, and quality attributes have a significant positive impact on willingness to pay more.